A young girl with short stature and Sprengel deformity: A case report (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Klippel-Feil syndrome (KFS) is a rare congenital disorder characterized by the classical triad of a short neck, limited neck mobility, and a low posterior hairline, though all features may not be present in every patient. We report a 5-year-old girl born to consanguineous parents who presented with poor growth and restricted neck movement for three years. Her height was 87 cm (SDS -4.6) and weight was 11 kg (SDS -2.8), indicating severe growth retardation. Clinical examination revealed a short neck, limited cervical movement, low posterior hairline, and congenital elevation of the left scapula. Intelligence was normal for age. Growth hormone stimulation test using clonidine showed a low peak response, while thyroid function tests were normal. Karyotyping revealed a normal female pattern (46, XX). Imaging demonstrated partial fusion of cervical vertebrae (C2-C4), Sprengel deformity, and cervical ribs. Ultrasonography showed absence of the left kidney with an infantile uterus, while echocardiography was normal. The patient was managed conservatively with multidisciplinary evaluation, growth hormone therapy, growth monitoring, physiotherapy, and genetic counseling. The prognosis is variable, and early identification of associated anomalies is essential for optimizing long-term outcomes.[J Assoc Clin Endocrinol Diabetol Bangladesh, January 2026; 5(1): 73-76]